If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4x + -1 = 4 Reorder the terms: -1 + 3x + -4x = 4 Combine like terms: 3x + -4x = -1x -1 + -1x = 4 Solving -1 + -1x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 4 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 4 + 1 -1x = 4 + 1 Combine like terms: 4 + 1 = 5 -1x = 5 Divide each side by '-1'. x = -5 Simplifying x = -5
| 3X^3-X^2-18X+9=0 | | 0.10x+7.5-0.15x=6 | | 0.02x+2-0.1x=0.7 | | 6xy-9y= | | 9q-8=18 | | 10(t-2)+5=5(3t+2)-9 | | (4y+4)-(2+3y)=11 | | 12-(x-4)=5x+2(x+16) | | 4P-8=20 | | (3d-7)-(d-2d)= | | x^2-44x+1600=0 | | 3x-5=7x+2 | | 0=-6+x^2+ABS(x) | | 6-x^2=ABS(x) | | 2x+29=9x+50 | | 9z-z=-3+5z-1-5 | | 4x^2+64y^2=64 | | 3.2x=2.24 | | 25=.99x | | 160=120+.15x | | 160=120 | | 6a-18=2a-10a+11 | | y^2=x+25 | | 2x-3y+0=0 | | -3x+y+0=0 | | 3c^6-6c^5-45c^4= | | 0.10*0.5+0.35g=0.15*g+0.5 | | 45d^3+36d^2-5d-4=0 | | logx=77 | | logqe=0.001 | | -2=1.6x+1 | | -3=1.6x+1 |